Understandability and Transparency of the Financial Statements of Charities - Sinclair, Rowena Margaret Sylvia (Auckland University of Technology, 2010)
Access to charities' financial statements has recently become possible in New Zealand due to the development of a Charities Register. However, the ability to discharge accountability through financial statements depends on the financial statements being transparent and understandable, which is not currently the case. This research focused on four complexities that impact on the transparency and understandability of charities' financial statements: the accounting basis; valuation of property, plant and equipment; fund accounting; and how charities report to stakeholders, in particular, the expenditure overheads ratio. The focus of this study was firstly, on gaining an understanding of what accounting treatments charities have adopted to deal with each of these complexities, but more importantly why charities chose these particular accounting treatments. This was achieved by conducting seventy-five interviews with eighty-four participants in the charities’ sector, in order to understand why charities act as they do. This study determined there were three key reasons behind the choices that charities make in accounting treatment. The first relates to the poor knowledge of appropriate professional standards by accountants working in the charities sector. This lack of professionalism must be addressed by accounting professional bodies to ensure the integrity of the accounting profession is maintained. The second is the low level of financial literacy among preparers and users of charities' financial statements. There is a need for charities and their stakeholders, to understand charities' financial statements to ensure charities produce meaningful financial statements that can be utilised for decision making. Third, it is the aim of many charities to 'look poor' as they seek to gain more funding. This impacts the accounting method charities use and so goes against the requirement for neutrality and freedom from bias when preparing financial statements. Accountability is seen as important for the charities sector in maintaining the confidence and financial support of the public by giving an account of charities' activities. For accountability to be successful it needs to be discharged. This study developed a charitable accountability model for charities to utilise in ensuring that accountability is appropriately discharged. This included the need for performance accountability where charities assess, and report on, their performance to ensure that they are making a positive difference in their beneficiaries' lives. Charities need to be proactive in communicating the success of their outcomes and outputs to attract monies and to differentiate themselves from other charitable organisations. Donors and funders also need to ensure that they are supporting financially viable charities who are prudently managing their future and achieving great success in their activities. Above all it is important that donors and funders donate to a good charity, not just to a great cause.
Keywords: Charities; Accountability; Discharge documents; Financial statements; Discharge mechanisms; Stakeholders